Modern Clan Politics : The Power of "Blood" in Kazakhstan and Beyond - Schatz, Edward (Book collections on Project MUSE., 2004)
"Edward Schatz explores the politics of kinbased clan divisions in the post-Soviet state of Kazakhstan. Drawing from extensive ethnographic and archival research, interviews, and wide-ranging secondary sources, he highlights a politics that poses a two-tiered challenge to current thinking about modernity and Central Asia. First, asking why kinship divisions do not fade from political life with modernization, he shows that the state actually constructs clan relationships by infusing them with practical political and social meaning. By activating the most important quality of clans - their "concealability"--The state is itself responsible for the vibrant politics of these subethnic divisions that have emerged and flourished in post-Soviet Kazakhstan." "Political scientists, sociologists, anthropologists, policy makers, and others who study state power and identity groups will find a wealth of empirical material and conceptual innovation for discussion and debate."--Jacket